Historical University of Latvia student solitary confinement cell - Rubenis, Rūdolfs; Livdāne, Sarmīte; Loris, Klāvs; Damberga, Andra; Lazdiņa, Baiba (LU Akadēmiskais apgāds, 2021)
The University of Latvia has 19th-century historical witness regarding the daily life of students during studies - the historical student solitary confinement cell. The origins of the student solitary confinement cell are found in medieval Germany, when universities were entitled to detain students into cells for the misdeeds during the studies. The idea was realized in the 19th century, which coincided with the time when German academic influence spread in the Baltics. During the occupation of the USSR, this history phenomenon was forgotten or distorted, but it is now rehabilitated. The Museum of the University of Latvia with the University of Latvia Academic Press has issued booklet, which introduces everyone with this forgotten history page in the history of Latvia's higher education.